Preparation method and application of high-dispersity cerium-based coordination polymer
The high-temperature reaction of plant phenol with organic ligands such as cerium chloride heptahydrate and 2-aminoterephthalic acid in the cerium-based coordination polymer was formed, and the cerium-based coordination polymer was solved. The problem of poor agglomeration and defluorination effects of position polymers in water environments has achieved the effect of significantly improving the fluorine adsorption capacity and fluorination removal performance.
Patent Information
- Application Number
- CN202411373684.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-10
AI Technical Summary
The existing cerium-based coordination polymers are prone to agglomeration in water environments and the structure π-π accumulation leads to difficulties in diffusion of fluorine ions, which limits their fluorine removal activity and has poor defluorination effect under neutral alkaline conditions.
Plant phenol is used to react with organic ligands such as cerium chloride heptahydrate and 2-aminoterephthalic acid to form a highly dispersible cerium-based coordination polymer, and cross-linking of phenolic molecules with cerium ions and organic ligands. Coordinate to improve its dispersion and fluorine removal properties in water.
The fluorine adsorption capacity and fluorine removal performance of the cerium-based coordination polymer are significantly improved, the reaction time is shortened, and excellent fluorine removal performance is shown in acidic-neutral-weak alkaline environments.
Smart Images

Figure CN119285969A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental composite functional materials, and in particular relates to a preparation method of a highly dispersible cerium-based coordination polymer and application thereof. Background Art
[0002] Water is an important resource necessary for human survival, reproduction and development. The fluorine element contained in drinking water is a substance necessary for maintaining life, but excessive fluorine intake can cause fluorosis, fluorosis, thyroid lesions and even death. Therefore, the World Health Organization (WHO) sets the maximum contaminant level (MCL) of fluoride in drinking water at 1.5 mg / L. The problem of how to treat fluoride-containing wastewater needs to be solved urgently. Traditional precipitation or coagulation methods are difficult to reduce the fluoride level to the limit specified by WHO at an economic cost. Adsorption method is considered to be one of the most effective technologies for treating fluoride-containing wastewater due to its low material cost, controllable operating conditions and high removal rate. Studies have found that cerium metal ions and organic ligands can form a class of regularly structured coordination polymers, such as metal organic frameworks, through coordination self-assembly. Compared with traditional fluoride removal materials such as activated alumina, activated carbon, and rare earth metal oxides, cerium-based coordination polymers have rich surface functional groups, orderly pore structures and high specific surface areas. In recent years, they have gradually developed into an emerging water treatment agent. First, cerium ions, as a Lewis hard acid, have a large ionic radius and a large number of extranuclear electron orbitals, and have a unique affinity for Lewis hard base-fluoride ions, which can effectively remove fluoride from water through ligand exchange. Second, the pH of surface water / groundwater is mainly moderately alkaline (pH 6-9), and commonly used adsorbents often have a higher adsorption capacity for fluorine under acidic conditions, and the defluorination effect is significantly worse under moderately alkaline conditions. The coordination polymers formed by cerium ions and organic ligands show an adsorption capacity equivalent to that under acidic conditions in moderately alkaline fluoride-containing wastewater. For example, the study of Tang et al. (Xiaofeng Tang, Wu Xia, Xiaolin Qu, et al. Chemosphere, 2023, 312: 137335) showed that Ce-BDC formed by terephthalic acid (BDC) and Ce ions exhibited pH defluorination stability superior to other cerium-based coordination polymers, and the fluctuation range of defluorination adsorption capacity in the pH range of 3-9 was about 15%, while other cerium-based coordination polymers fluctuated by more than 60%. For example, Jeyaseelan et al. (Antonysamy Jeyaseelan, Mu. Naushad, Tansir Ahamad, et al. Environ. Sci.: Water Res. Technol., 2021, 7(2): 384-395) found that the adsorption capacity of Ce-ABDC formed by 2-aminoterephthalic acid (NTA) and Ce ions was about 5% higher than that of Ce-BDC synthesized under the same conditions when treating real fluoride wastewater, and had the same pH defluorination stability.
[0003] However, cerium-based coordination polymers are often micrometer or even nanometer-sized, and are prone to agglomeration in water environment systems due to their high tendency to aggregate. In addition, the structure of cerium-based coordination polymers usually has deep entrapment of active sites due to π-π stacking interactions, making it difficult for fluoride ions to diffuse, restricting their contact with fluoride ions, and greatly limiting the defluorination activity of cerium-based metal organic frameworks. Based on this, developing a cerium-based metal organic framework with good dispersibility in water phase can significantly improve the actual defluorination performance. Summary of the invention
[0004] The first purpose of the present invention is to provide a method for preparing a highly dispersed cerium-based coordination polymer, which has a simple preparation process, mild conditions and a wide range of raw material sources.
[0005] The second object of the present invention is to provide a highly dispersible cerium-based coordination polymer, the dispersion performance of the polymer in water is improved, and the defluorination performance is significantly improved.
[0006] The third purpose of the present invention is to propose an application of a highly dispersed cerium-based coordination polymer in defluoridation of water bodies, thereby accelerating the adsorption rate of fluoride ions and shortening the reaction time.
[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a highly dispersible cerium-based coordination polymer comprises the following steps: first dissolving plant phenolic formaldehyde and cerium chloride heptahydrate in deionized water to obtain a mixed solution; then mixing the obtained mixed solution with an organic ligand solution, reacting the mixture at high temperature, and then washing and drying the mixture to obtain Ce-PNTA.
[0009] Furthermore, the plant phenolic aldehyde is selected from one of schisandra acid, caffeic acid, tea polyphenols and tannic acid.
[0010] Furthermore, the organic ligand solution is a solution obtained by dissolving 2-aminoterephthalic acid in N,N-dimethylformamide.
[0011] Furthermore, the mass ratio of the plant phenolic formaldehyde to the cerium chloride heptahydrate is 4-10:11-55.
[0012] Furthermore, the temperature of the high temperature reaction after mixing is 120° C., and the reaction time is 24 hours.
[0013] Furthermore, the washing step is: washing with N,N-dimethylformamide, ethanol and deionized water in sequence, the washing times are 3 times, and the solvent is changed once every 12 hours; the drying method is: drying at 80°C in vacuum for 12 hours.
[0014] Furthermore, the preparation method of any of the above-mentioned highly dispersible cerium-based coordination polymers comprises the following steps:
[0015] (1) Weighing plant phenolic aldehyde and cerium chloride heptahydrate according to the ratio, adding deionized water, and stirring until fully dissolved;
[0016] (2) dissolving 2-aminoterephthalic acid with N,N-dimethylformamide to obtain an organic ligand solution, and mixing the organic ligand solution with the solution obtained by fully dissolving the ligand in step (1) to obtain a mixed solution;
[0017] (3) transferring the mixed solution obtained in step (2) into a high-pressure reactor containing a polytetrafluoroethylene liner, reacting at 120° C. for 24 h, then taking out and naturally cooling to room temperature to obtain a product;
[0018] (4) The product obtained in step (3) was washed three times with N,N-dimethylformamide, ethanol and deionized water in sequence, and vacuum dried at 80° C. for 12 h to obtain Ce-PNTA.
[0019] Furthermore, in step (2), the mass ratio of plant phenolic formaldehyde to 2-aminoterephthalic acid in the mixed solution is 10:11 to 4:11; the mass ratio of cerium chloride heptahydrate to 2-aminoterephthalic acid is 5:1 to 1:1; and the volume ratio of deionized water to N,N-dimethylformamide is 5:12.
[0020] Furthermore, a highly dispersible cerium-based coordination polymer prepared by any of the above methods.
[0021] Furthermore, the highly dispersed cerium-based coordination polymer is used in defluoridation of water.
[0022] Compared with the prior art, the advantages of the present invention are as follows:
[0023] 1) The present invention uses a certain concentration of plant phenolic solution as a dispersant and cross-linking agent, adds it to a cerium chloride heptahydrate solution, and forms a separated and orderly network arrangement structure between the cerium single ions through the rich phenolic hydroxyl structure of the phenolic molecule and the multi-dentate cross-linking of the cerium single ions, and further coordinates with the organic ligand NTA to prepare a highly dispersible cerium-based coordination polymer (Ce-PNTA). Compared with the original cerium-based coordination polymer, the new cerium-based polymer has greatly improved dispersibility in water and greatly improved fluorine removal performance, and the maximum fluorine adsorption capacity has increased by 91.92%.
[0024] 2) The present invention utilizes the bridging effect between the galloyl group on the plant phenolic molecule and the cerium ion to expand the crystallite spacing of the cerium-based coordination polymer, weaken the π-π stacking interaction, further promote the rapid diffusion and mass transfer of ions between crystals, accelerate the fluoride ion adsorption rate, and shorten the reaction time by 41.67%.
[0025] 3) The highly dispersed cerium-based coordination polymer prepared by the present invention has excellent fluorine removal performance in acidic, neutral and weakly alkaline environments.
[0026] 4) The plant-derived phenolic aldehyde used in the present invention is environmentally friendly, widely available, low-cost, and has a simple preparation process and mild conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of fluoride ion adsorption isotherms of the parent Ce-NTA prepared in Example 1 of the present invention and the Ce-PNTA prepared in Example 3;
[0028] Figure 2 Schematic diagram of fluoride ion adsorption kinetics of the parent Ce-NTA prepared in Example 1 of the present invention and the Ce-PNTA prepared in Example 3;
[0029] Figure 3 Schematic diagram of the experiment on the effect of solution pH of Ce-PNTA prepared in Example 3 of the present invention;
[0030] Figure 4 This is a comparison diagram of particle dispersion of the parent Ce-NTA prepared in Example 1 of the present invention and the Ce-PNTA solution prepared in Example 3 after centrifugal ultrasonic dispersion;
[0031] Figure 5 TEM images of the matrix Ce-NTA prepared in Example 1 and the Ce-PNTA prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.
[0033] Unless otherwise specified, the raw materials or reagents used in the following examples are commercially available products.
[0034] The fluoride adsorption performance of the series of Ce-PNTA prepared in the following examples was tested. Unless otherwise specified, the initial fluoride concentration was selected as 150 mg / L, the pH was 9, the solid-liquid ratio was selected as 0.5 g / L, the experimental temperature was 25°C, the shaking speed was 180 rpm, and all samples were filtered with a 0.22 μm filter membrane before measurement.
[0035] Example 1
[0036] A method for preparing a highly dispersible cerium-based coordination polymer comprises the following steps:
[0037] (1) 0.50 g of tannic acid and 2.75 g of cerium chloride heptahydrate were dissolved in 25 mL of deionized water, and stirred for 1 h to allow the tannic acid and cerium ions to fully react to obtain a mixed solution;
[0038] (2) dissolving 0.55 g of 2-aminoterephthalic acid in 60 mL of N,N-dimethylformamide to obtain an organic ligand solution; adding the organic ligand solution to the mixed solution prepared in step (1), and mixing again to obtain a uniform mixture;
[0039] (3) placing the mixed solution obtained in step (2) into a polytetrafluoroethylene reactor and reacting at a high temperature of 120° C. for 24 hours to obtain a product;
[0040] (4) The product obtained in step (3) was washed with N,N-dimethylformamide, ethanol, and deionized water in sequence until neutral, and dried at 80° C. for 12 h to obtain Ce-PNTA.
[0041] The saturated adsorption capacity of fluoride by Ce-PNTA prepared in this example is 95.37 mg / g, while the saturated adsorption capacity of fluoride by Ce-NTA prepared by the same method without adding tannic acid under the same conditions is 92.59 mg / g. In comparison, the adsorption capacity is increased by 3.00%.
[0042] Example 2
[0043] A method for preparing a highly dispersible cerium-based coordination polymer comprises the following steps:
[0044] (1) 0.30 g of tannic acid and 2.20 g of cerium chloride heptahydrate were dissolved in 25 mL of deionized water and stirred for 1 h to allow the tannic acid and cerium ions to react fully to obtain a mixed solution.
[0045] (2) Dissolve 0.55 g of 2-aminoterephthalic acid in 60 mL of N,N-dimethylformamide to obtain an organic ligand solution; add the organic ligand solution to the mixed solution prepared in step (1), and mix again until uniform.
[0046] (3) The mixed solution in step (2) is placed in a polytetrafluoroethylene reactor and reacted at a high temperature of 120° C. for 24 hours to obtain a product.
[0047] (4) The product obtained in step (3) was washed with N,N-dimethylformamide, ethanol, and deionized water in sequence until neutral, and dried at 80° C. for 12 h to obtain Ce-PNTA.
[0048] The saturated adsorption capacity of fluoride by Ce-PNTA prepared in this example is 103.36 mg / g, which is 11.63% higher than the adsorption capacity of the parent Ce-NTA mentioned in Example 1.
[0049] Example 3
[0050] A method for preparing a highly dispersible cerium-based coordination polymer comprises the following steps:
[0051] (1) 0.25 g of tannic acid and 1.65 g of cerium chloride heptahydrate were dissolved in 25 mL of deionized water, and stirred for 1 h to allow the tannic acid and cerium ions to fully react to obtain a mixed solution;
[0052] (2) dissolving 0.55 g of 2-aminoterephthalic acid in 60 mL of N,N-dimethylformamide to obtain an organic ligand solution; adding the organic ligand solution to the mixed solution prepared in step (1), and mixing again;
[0053] (3) placing the uniformly mixed solution of step (2) into a polytetrafluoroethylene reactor, and reacting at a high temperature of 120° C. for 24 hours to obtain a product;
[0054] (4) The product obtained in step (3) was washed with N,N-dimethylformamide, ethanol, and deionized water in sequence until neutral, and dried at 80° C. for 12 h to obtain Ce-PNTA.
[0055] The saturated adsorption capacity of fluoride by Ce-PNTA prepared in this example is 177.70 mg / g, which is 91.92% higher than the adsorption capacity of the parent Ce-NTA mentioned in Example 1.
[0056] like Figure 1 As shown, the Ce-PNTA obtained in this example and the parent Ce-NTA prepared in Example 1 were subjected to isothermal adsorption experiments, and the initial fluoride concentration was selected to be 15-150 mg / L. Figure 1 The results show that Ce-PNTA exhibits a better adsorption effect than Ce-NTA. The reason is that the phenolic hydroxyl groups in the phenolic aldehyde molecules are cross-linked with the multi-dentate cerium ions, so that the cerium ions form a separated and orderly network structure, and a highly dispersed cerium-based coordination polymer is obtained. The Langmuir isotherm adsorption model and the Freundlich isotherm adsorption model were used to fit the experimental results. The Langmuir model fitting R of Ce-PNTA 2 The Freundlich model fitting R is 0.919. 2 is 0.995, and the adsorption isotherm of Ce-PNTA is more consistent with the Freundlich isotherm adsorption model, which indicates that the adsorption process involves multiple coordination of cerium ions and fluoride ions.
[0057] Example 4
[0058] A method for preparing a highly dispersible cerium-based coordination polymer comprises the following steps:
[0059] (1) 0.2 g of tannic acid and 0.55 g of cerium chloride heptahydrate were dissolved in 25 mL of deionized water and stirred for 1 h to allow the tannic acid and cerium ions to react fully to obtain a mixed solution.
[0060] (2) dissolving 0.55 g of 2-aminoterephthalic acid in 60 mL of N,N-dimethylformamide to obtain an organic ligand solution; adding the organic solution to the mixed solution prepared in step (1) and mixing again;
[0061] (3) The mixed solution in step (2) is placed in a polytetrafluoroethylene reactor and reacted at a high temperature of 120° C. for 24 hours to obtain a product.
[0062] (4) The product obtained in step (3) was washed with N,N-dimethylformamide, ethanol, and deionized water in sequence until neutral, and dried at 80° C. for 12 h to obtain Ce-PNTA.
[0063] The saturated adsorption capacity of fluoride by Ce-PNTA prepared in this example is 127.23 mg / g, which is 37.41% higher than the adsorption capacity of the parent Ce-NTA mentioned in Example 1.
[0064] From the comparison of the above embodiments, it can be seen that the addition of plant phenolic formaldehyde is conducive to obtaining a cerium-based coordination polymer with better performance, but different raw material ratios or doping ratios will bring different effects.
[0065] Example 5
[0066] A method for preparing a highly dispersible cerium-based coordination polymer comprises the following steps:
[0067] (1) 0.2 g of tea polyphenols and 2.75 g of cerium chloride heptahydrate were dissolved in 25 mL of deionized water, and stirred for 1 h to allow the tea polyphenols and cerium ions to fully react to obtain a mixed solution;
[0068] (2) dissolving 0.55 g of 2-aminoterephthalic acid in 60 mL of N,N-dimethylformamide to obtain an organic ligand solution; adding the organic ligand solution to the mixed solution prepared in step (1), and mixing again;
[0069] (3) placing the uniformly mixed solution of step (2) into a polytetrafluoroethylene reactor, and reacting at a high temperature of 120° C. for 24 hours to obtain a product;
[0070] (4) The product obtained in step (3) was washed with N,N-dimethylformamide, ethanol, and deionized water in sequence until neutral, and dried at 80° C. for 12 h to obtain Ce-PNTA.
[0071] The saturated adsorption capacity of fluoride by Ce-PNTA prepared in this example is 95.23 mg / g, which is 2.85% higher than the adsorption capacity of the parent Ce-NTA mentioned in Example 1.
[0072] Example 6
[0073] A method for preparing a highly dispersible cerium-based coordination polymer comprises the following steps:
[0074] (1) 0.4 g of schisandra acid and 1.65 g of cerium chloride heptahydrate were dissolved in 25 mL of deionized water, and stirred for 1 h to allow schisandra acid and cerium ions to fully react to obtain a mixed solution;
[0075] (2) dissolving 0.55 g of 2-aminoterephthalic acid in 60 mL of N,N-dimethylformamide to obtain an organic ligand solution; adding the organic ligand solution to the mixed solution prepared in step (1), and mixing again;
[0076] (3) placing the uniformly mixed solution of step (2) into a polytetrafluoroethylene reactor, and reacting at a high temperature of 120° C. for 24 hours to obtain a product;
[0077] (4) The product obtained in step (3) was washed with N,N-dimethylformamide, ethanol, and deionized water in sequence until neutral, and dried at 80° C. for 12 h to obtain Ce-PNTA.
[0078] The saturated adsorption capacity of fluoride by Ce-PNTA prepared in this example is 134.77 mg / g, which is 45.56% higher than the adsorption capacity of the parent Ce-NTA mentioned in Example 1.
[0079] Example 7
[0080] A method for preparing a highly dispersible cerium-based coordination polymer comprises the following steps:
[0081] (1) 0.25 g of schisandra acid and 1.65 g of cerium chloride heptahydrate were dissolved in 25 mL of deionized water, and stirred for 1 h to allow schisandra acid and cerium ions to fully react to obtain a mixed solution;
[0082] (2) dissolving 0.55 g of 2-aminoterephthalic acid in 60 mL of N,N-dimethylformamide to obtain an organic ligand solution; adding the organic ligand solution to the mixed solution prepared in step (1), and mixing again;
[0083] (3) placing the uniformly mixed solution of step (2) into a polytetrafluoroethylene reactor, and reacting at a high temperature of 120° C. for 24 hours to obtain a product;
[0084] (4) The product obtained in step (3) was washed with N,N-dimethylformamide, ethanol, and deionized water in sequence until neutral, and dried at 80° C. for 12 h to obtain Ce-PNTA.
[0085] The saturated adsorption capacity of fluoride by Ce-PNTA prepared in this example is 156.29 mg / g, which is 68.80% higher than the adsorption capacity of the parent Ce-NTA mentioned in Example 1.
[0086] Example 8
[0087] A method for preparing a highly dispersible cerium-based coordination polymer comprises the following steps:
[0088] (1) 0.5 g of caffeic acid and 2.75 g of cerium chloride heptahydrate were dissolved in 25 mL of deionized water, and stirred for 1 h to allow schisandra acid and cerium ions to fully react to obtain a mixed solution;
[0089] (2) dissolving 0.55 g of 2-aminoterephthalic acid in 60 mL of N,N-dimethylformamide to obtain an organic ligand solution; adding the organic ligand solution to the mixed solution prepared in step (1), and mixing again;
[0090] (3) placing the uniformly mixed solution of step (2) into a polytetrafluoroethylene reactor, and reacting at a high temperature of 120° C. for 24 hours to obtain a product;
[0091] (4) The product obtained in step (3) was washed with N,N-dimethylformamide, ethanol, and deionized water in sequence until neutral, and dried at 80° C. for 12 h to obtain Ce-PNTA.
[0092] The saturated adsorption capacity of fluoride by Ce-PNTA prepared in this example is 113.44 mg / g, which is 22.52% higher than the adsorption capacity of the parent Ce-NTA mentioned in Example 1.
[0093] Example 9
[0094] A method for preparing a highly dispersible cerium-based coordination polymer comprises the following steps:
[0095] (1) 0.25 g of caffeic acid and 1.65 g of cerium chloride heptahydrate were dissolved in 25 mL of deionized water, and stirred for 1 h to allow schisandra acid and cerium ions to fully react to obtain a mixed solution;
[0096] (2) dissolving 0.55 g of 2-aminoterephthalic acid in 60 mL of N,N-dimethylformamide to obtain an organic ligand solution; adding the organic ligand solution to the mixed solution prepared in step (1), and mixing again;
[0097] (3) placing the uniformly mixed solution of step (2) into a polytetrafluoroethylene reactor, and reacting at a high temperature of 120° C. for 24 hours to obtain a product;
[0098] (4) The product obtained in step (3) was washed with N,N-dimethylformamide, ethanol, and deionized water in sequence until neutral, and dried at 80° C. for 12 h to obtain Ce-PNTA.
[0099] The saturated adsorption capacity of fluoride by Ce-PNTA prepared in this example is 142.35 mg / g, which is 53.74% higher than the adsorption capacity of the parent Ce-NTA mentioned in Example 1.
[0100] Example 10
[0101] Adsorption kinetics experiments were conducted using Ce-PNTA prepared in Example 3 and Ce-NTA, the parent material mentioned in Example 1. 1 mL of supernatant was taken at 0, 1, 2, 3, 5, 7, 10, 15, 20, 25, 30, 35 min, etc., and the fluoride ion concentration of the solution at that time was measured to obtain an adsorption kinetics graph, as shown in FIG. Figure 2 shown.
[0102] The results show that Ce-PNTA can deeply purify fluoride-containing wastewater within 70 minutes, which is 41.67% shorter than that of Ce-NTA. The reason is that the bridging effect between the galloyl groups on the plant phenolic formaldehyde and the cerium ions expands the crystallite spacing of the cerium-based coordination polymer, weakens its π-π stacking interaction, promotes the rapid diffusion and mass transfer of fluoride ions, and accelerates the adsorption rate.
[0103] Embodiment 11
[0104] The Ce-PNTA prepared in Example 3 and the parent Ce-NTA mentioned in Example 1 were respectively used to carry out water dispersibility experiments, Zeta potential experiments and TEM characterization.
[0105] Water dispersibility experiment: 0.25 g of Ce-NTA and Ce-PNTA were placed in centrifuge tubes containing 50 mL of water, respectively, and taken out after ultrasonic treatment for 10 min to observe the dispersion of particles in the solution.
[0106] Zeta potential experiment: Take 5g of Ce-NTA and Ce-PNTA respectively and add them into a 250mL beaker, then add 100mL of deionized water into the beaker and stir to make the powder particles disperse evenly in the deionized water. Use a zeta potential meter to measure the zeta potential values of the samples respectively.
[0107] TEM characterization: First, the dried Ce-NTA and Ce-PNTA were added to ethanol and ultrasonically dispersed for 1 to 2 minutes. Then, a few drops of the dispersed solution were dropped on a copper grid and the ethanol was allowed to evaporate. Finally, the microscopic morphology of Ce-NTA and Ce-PNTA was observed and analyzed in detail using TEM.
[0108] The results are as follows Figure 4 As shown in the figure, the supernatant of Ce-PNTA is more turbid and has better dispersibility in water than Ce-NTA. The absolute value of the zeta potential of Ce-NTA is 0.106, and the absolute value of the zeta potential of Ce-PNTA is 3.11. The more charges on the surface of the particles, the higher the absolute value of the zeta potential, the greater the repulsive force between the particles, and the better the dispersibility. Figure 5 As shown, it can be seen that the cerium-based coordination polymer exhibits good dispersion, and the contact surface that can bind to anions is fully exposed relative to Ce-NTA.
[0109] Example 12
[0110] The Ce-PNTA obtained in Example 3 was used to conduct a pH effect experiment. Figure 3 The fluoride ion concentration of the solution after adsorption equilibrium was measured to obtain the saturated adsorption amount of fluoride ions at different solution pH values.
[0111] The results show that the adsorption capacity of Ce-PNTA for fluoride ions gradually decreases with the increase of pH, but the decrease is less than 25 mg / g, about 12.01%. Ce-PNTA can be used in a wide pH range. It has excellent defluorination performance in acidic, neutral and weakly alkaline environments. Therefore, the use of Ce-PNTA for defluorination provides a new and feasible idea for the purification of fluoride-containing wastewater.
[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a highly dispersible cerium-based coordination polymer, characterized in that: The plant phenolic formaldehyde and cerium chloride heptahydrate are first dissolved in deionized water to obtain a mixed solution; the obtained mixed solution is then mixed with an organic ligand solution, reacted at high temperature, and then washed and dried to obtain Ce-PNTA.
2. The method for preparing a highly dispersible cerium-based coordination polymer according to claim 1, characterized in that: The plant phenolic aldehyde is selected from one of schisandra acid, caffeic acid, tea polyphenols and tannic acid.
3. The method for preparing a highly dispersible cerium-based coordination polymer according to claim 1, characterized in that: The organic ligand solution is a solution obtained by dissolving 2-aminoterephthalic acid in N,N-dimethylformamide.
4. The method for preparing a highly dispersible cerium-based coordination polymer according to claim 1, characterized in that: The mass ratio of the plant phenolic formaldehyde to the cerium chloride heptahydrate is 4-10:11-55.
5. The method for preparing a highly dispersible cerium-based coordination polymer according to claim 1, characterized in that: The temperature of the high temperature reaction after mixing is 120°C and the reaction time is 24h.
6. The method for preparing a highly dispersible cerium-based coordination polymer according to claim 1, characterized in that: The washing step is: washing with N,N-dimethylformamide, ethanol and deionized water in sequence, the washing times are 3 times, and the solvent is changed once every 12 hours; the drying method is: drying at 80° C. in vacuum for 12 hours.
7. The method for preparing a highly dispersed cerium-based coordination polymer according to any one of claims 1 to 6, characterized in that: Here are the steps: (1) Weighing plant phenolic aldehyde and cerium chloride heptahydrate according to the ratio, adding deionized water, and stirring until fully dissolved; (2) dissolving 2-aminoterephthalic acid with N,N-dimethylformamide to obtain an organic ligand solution, and mixing the organic ligand solution with the solution obtained by fully dissolving the ligand in step (1) to obtain a mixed solution; (3) transferring the mixed solution obtained in step (2) into a high-pressure reactor containing a polytetrafluoroethylene liner, reacting at 120° C. for 24 h, then taking out and naturally cooling to room temperature to obtain a product; (4) The product obtained in step (3) was washed three times with N,N-dimethylformamide, ethanol and deionized water in sequence, and vacuum dried at 80° C. for 12 h to obtain Ce-PNTA.
8. The method for preparing a highly dispersible cerium-based coordination polymer according to claim 7, characterized in that: In the step (2), the mass ratio of plant phenolic formaldehyde to 2-aminoterephthalic acid in the mixed solution is 10:11 to 4:11; the mass ratio of cerium chloride heptahydrate to 2-aminoterephthalic acid is 5:1 to 1:1; and the volume ratio of deionized water to N,N-dimethylformamide is 5:
12.
9. A highly dispersible cerium-based coordination polymer prepared by the method according to any one of claims 1 to 8.
10. Use of the highly dispersible cerium-based coordination polymer according to claim 9 in defluoridation of water.